The Influence of Personality Traits on Entrepreneurial Intention - DEMIRTAS, Ozgur; KARACA, Mustafa; OZDEMIR, A Hakan (International Journal of Management and Sustainability, 2017)
Within the context of research on person-to-organization fit, it is suggested that the better the match between individuals’ attitudes, values, knowledge, skills, abilities and personality with the organization, the higher the individual and organizational outcomes will be. In this perspective, this research assesses that as the match between an entrepreneur’s personal characteristics and the requirements of being an entrepreneur gets better, the enterprise is thought to be more successful. Especially to the extent that the entrepreneurs are better off on a number of distinct dimensions of individual differences (i.e. self-efficacy, ability to recognize opportunities, personal perseverance, human and social capital, social skills and innovativeness), person-entrepreneur fit will be better and consequently the success rate will be higher. From this point of view, this study tries to find out how personality traits affect entrepreneurial intentions. This framework offers potentially valuable new ways of assisting entrepreneurs in their efforts to exploit opportunities through establishing new ventures. The results indicate that self-efficacy, ability to detect an opportunity, personal perseverance, human capital, social capital and social skills positively affect entrepreneurial intentions.